Pastoral Bearings : Lived Religion and Pastoral Theology. - (EDS), HUMMEL/MAYNARD/ ET AL (Rowman & Littlefield Pub. Group, 2010)
The study of lived religion is an enterprise which attempts to elucidate how "ordinary" men and women in all times and places draw on religious behavior, media, and meanings to make sense of themselves and their world. Through the influence of liberationtheology and postmodernism, pastoral theologians--like other scholars of religion--have begun more closely to examine the particularity of religious practice that is reflected through the rubric of lived religion. Pastoral Bearings offers up ten studies that exemplify the usefulness of the lived religion paradigm to the field of pastoral theolo.